2023
DOI: 10.1177/11297298231152280
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial comparing ultrasound-guided versus traditional palpatory methods of posterior tibial artery cannulation in adult patients

Abstract: Background: The palpation method of posterior tibial artery cannulation has not yet been compared to ultrasound-guided posterior tibial artery cannulation in adults. This research examined whether using ultrasound to cannulate the posterior tibial artery enhances first-pass cannulation success and lowers total procedure time. Methods: In this randomized controlled experiment, 76 adult patients were included who were undergoing surgery under general anesthesia and required artery cannulation. Cannulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The authors found that the successful PTA cannulation rate on the first attempt was comparable between the USG and palpation groups. By contrast, the cannulation time and total procedural time were significantly higher in the palpation group [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the successful PTA cannulation rate on the first attempt was comparable between the USG and palpation groups. By contrast, the cannulation time and total procedural time were significantly higher in the palpation group [ 16 ].…”
Section: Discussionmentioning
confidence: 99%